Pemeriksaan patologi sampel urin pada pasien menggunakan metode makroskopis, carik celup dan mikroskopis di Balai Laboratorium Kesehatan dan Kalibrasi Yogyakarta - Dewi, Arvin Mustika (Maliki Interdisciplinary Journal, 2023)
Urine is a liquid excreted that contains various components of substances and can be used to find out important information about human health through urinalysis. Urinalysis is an examination of urine that can be done macroscopically, dipstick and microscopically. There were 25 urine samples that had been examined at the Yogyakarta Health and Calibration Laboratory Center. The results of the examination showed that 36% of urine had anon-standard color, 36% had an inappropriate pH, 24% of the urine samples contained protein, 4% contained glucose and ketones, 4% abnormal urobilin, 8% of the samples contained bilirubin and nitrste, 44% the sample contains blood, and 36% of the samples contains leukocyte esterase, 40% contains leukocyte cells, 16% contains erythrocyte cells, 28% contains epithelium, 40% contains mucus, 92% contains crystal, 24% contains hyaline cylinders, 48% contains cylinders granules, 4% contain epithelial cylinders, 12% contain leukocyte cylinders, and 0% contain erythrocyte cylinders. The results of these examinations can be used to detect various kinds of diseases in a person’s body and can used as a basis for diagnosis.